2021
DOI: 10.1001/jamapsychiatry.2020.4064
|View full text |Cite
|
Sign up to set email alerts
|

Association of Heavy Drinking With Deviant Fiber Tract Development in Frontal Brain Systems in Adolescents

Abstract: IMPORTANCE Maturation of white matter fiber systems subserves cognitive, behavioral, emotional, and motor development during adolescence. Hazardous drinking during this active neurodevelopmental period may alter the trajectory of white matter microstructural development, potentially increasing risk for developing alcohol-related dysfunction and alcohol use disorder in adulthood.OBJECTIVE To identify disrupted adolescent microstructural brain development linked to drinking onset and to assess whether the disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 52 publications
1
29
0
1
Order By: Relevance
“…Existing studies support that there is an association between alcohol‐drinking patterns and different structural and functional impairments to the brain, especially in young adults who drink alcohol (Kim et al., 2020; Liu et al., 2018; Mashhoon et al., 2014; Tu et al., 2018; Zhao et al., 2021). Mashhoon et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies support that there is an association between alcohol‐drinking patterns and different structural and functional impairments to the brain, especially in young adults who drink alcohol (Kim et al., 2020; Liu et al., 2018; Mashhoon et al., 2014; Tu et al., 2018; Zhao et al., 2021). Mashhoon et al.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al. (2021) suggested that heavy alcohol drinking is associated with impairments to the microstructural integrity of brain WM in adolescent heavy drinkers. Simultaneously, Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we approached our analyses conservatively by using age- and sex-matched samples, which reduced power by limiting the sample sizes and biasing the ages toward the older ages and away from the younger ages commonly showing the greatest alcohol effects. Given the disturbed brain macrostructural and microstructural developmental trajectories related to initiation of heavy drinking, especially in young drinkers (Pfefferbaum et al, 2018; Zhao et al, in press), future studies are clearly warranted to seek selective cognitive or motor component processes that are concurrently disturbed with drinking.…”
Section: Discussionmentioning
confidence: 99%
“…During inference, the samples from CT domain are initially translated to MRI scans, which are then used to predict the segmentation mask by a segmentor trained on the MRI domain. MUNIT has been evaluated on the following medical datasets: LiTS [139] liver, NCANDA [140] and BraTS [141] brain, CHAOs [142] abdomen organs, and MS-CMRSeg [143,144] and MM-WHS [120,121,122] cardiac datasets, respectively.…”
Section: Multi-modal and Cross-modal Segmentationmentioning
confidence: 99%